The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1074/jbc.270.44.26377
|View full text |Cite
|
Sign up to set email alerts
|

A New Factor from Escherichia coli Affects Translocation of mRNA

Abstract: Reconstitution of protein synthesis from purified translation factors on ribosomes from Escherichia coli has revealed the requirement for a protein, W, that affects chain elongation and is essential to reconstitute the process (Ganoza, M. C., Cunningham, C., and Green, R. M. (1985) Proc. Natl. Acad. Sci. U.S.A. 82, 1648 -1652).We report that W has no effect on initiation complex formation by 30 or 70 S ribosomes or on the association of ribosomal subunits, peptide bond synthesis, or binding Ala-tRNA, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Ganoza et al [7] and Green et al [26] demonstrated that W facilitated the release of tRNAs from the E site and that this increased cognate binding at the A site. Certainly RbbA and W may act together as a functional homologue to yeast EF-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganoza et al [7] and Green et al [26] demonstrated that W facilitated the release of tRNAs from the E site and that this increased cognate binding at the A site. Certainly RbbA and W may act together as a functional homologue to yeast EF-3.…”
Section: Discussionmentioning
confidence: 99%
“…An active mechanism for the ejection of the E-site-bound deacyl-tRNA that forms after peptide bond synthesis was first proposed to be mediated by a soluble protein that is essential to reconstitute synthesis from purified E. coli components [6,7]. Interestingly, a fungi-specific ATPase, EF-3, has more recently been reported to accelerate the rate of deacyl-tRNA ejection from Saccharomyces cerevisiae ribosomes [8,9].…”
mentioning
confidence: 99%
“…The action of EFG may be preceded by movement of the deacyltRNA from the P site to the E site (163). This reaction is stimulated strongly by the RbbA protein, but it is not certain whether the RbbA protein ejects tRNAs only from the E site after peptide bond synthesis or from the P site also (57). In the former case, EFG may mediate translocation both of the deacyl-tRNA from the P site to the E site and of the peptidyltRNA from the A site to the P site.…”
Section: Translocationmentioning
confidence: 99%
“…Fungi have another elongation factor, eEF3, which is a ribosomedependent ATPase (29). This reaction is analogous to that first discovered in E. coli and called W, which ejects tRNAs from 70S ribosomes (57,58,74). (The name of the W protein [a truncated version of RbbA] was changed to reflect the fact that the protein is a ribosome-bound ATPase.)…”
Section: Decodingmentioning
confidence: 99%
“…The H. influenzae K46A YbaK mutant was prepared using Ni 2ϩ -nitrilotriacetic acid resin (Qiagen) as described before (28). E. coli elongation factor-Tu (EF-Tu) was isolated in the EF-Tu⅐GDP form from E. coli strain DH10B-T1 (Invitrogen) carrying pPROEX-HTb_EF-Tu (35,36). The protein was purified using Ni 2ϩ -nitrilotriacetic acid resin followed by removal of the His tag using the AcTEV protease (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%